STUDIES ON THE MODE OF ACTION OF DIPHTHERIA TOXIN : III. EFFECT ON SUBCELLULAR COMPONENTS OF PROTEIN SYNTHESIS FROM THE TISSUES OF INTOXICATED GUINEA PIGS AND RATS - Bowman, Catharine G. (The Rockefeller University Press, 1970)
The effect of diphtheria toxin on subcellular components of protein synthesis was determined. Polyribosomes prepared from intoxicated guinea pigs functioned normally in an in vitro assay system, while the activity of soluble enzymes (transferases) from toxin-treated animals was significantly reduced. At high toxin dosages, this reduction was widespread, but when levels of toxin comparable to those which might be generated in a natural infection were given, inhibition of soluble enzyme activity was found only in extracts from heart and skeletal muscle. Possible nonspecific inhibition in the assay system due to interference by free toxin or by a serum component was eliminated. Since it was possible to demonstrate reactivation of soluble enzyme activity with nicotinamide and toxin, it was suggested that diphtheria toxin acts in the intact sensitive animal in a manner analogous to its action in tissue culture or in cell-free systems. It was hypothesized that the lethal biochemical lesion of the toxin in sensitive animals was the inactivation of transferase enzymes, principally in the heart. It was also suggested that the lethal lesion induced in diphtheria-sensitive and resistant species may not be identical.